PELAYANAN KESEHATAN KOMPREHENSIF: PEMERIKSAAN DAN KONSELING OLEH APOTEKER SEBAGAI UPAYA PREVENTIF DI LLDIKTI XI KALIMANTAN SELATAN - Nur Ainah; Farida Istiqamah; Muhammad Hafiz Abiyyu Fathin Fawwazi; Erna Prihandiwati; Yugo Susanto; Amaliyah Wahyuni; Rakhmadhan Niah; Tedi Rustandi; Riza Alfian; Novia Ariani (Jurnal Bakti untuk Negeri, 2025)
Preventive health efforts are actions taken to avoid potential health problems that may affect ourselves or others in the future. A free health check-up was conducted in the LLDIKTI XI South Kalimantan area in Banjarmasin with the aim of raising awareness and understanding of the importance of maintaining health to prevent disease. The event began with a group exercise session, followed by free medical check-ups and counseling provided by pharmacists. A total of 48 participants took part in this activity, gaining insights into healthy lifestyles and the importance of regular health check-ups at health service centers. The results of the examinations served as a reference and reminder for participants to monitor their health regularly and improve their lifestyle habits. This initiative is expected to increase participants' awareness of the importance of disease prevention over treatment, with regular health check-ups serving as the first step to minimize future health risks.